Factors influencing the growth of Muslim friendly hospitality services in Malaysia - Ramli, Noriah; Zawawi, Majdah (2019)
Halal today is no longer focused on food and beverages manufacturing but also halal pharmaceuticals, cosmetics, logistics, consumer goods and Muslim friendly hospitality services. Changes in the Muslim lifestyle and spending ability have a positive impact on the growth in the global halal industry market. Advancement in communication technology, availability of online information on Muslim friendly hospitality globally, the increasing awareness on the needs of Muslim travellers including halal food, prayer facilities, Muslim friendly accommodation, Muslim friendly tourism products and activities, and Muslim friendly tour guide are identified as the major factors that attract Muslims to travel. The Muslim friendly hospitality services are Shariah guided requirement for tourism industry players in setting up an assurance system to preserve the integrity of products and services provided for Muslim travellers (Department of Standard Malaysia, MS 2610:2015 Muslim Friendly Hospitality Services_Requirements). From the economic point of view with more than 50 Muslim countries (no less than 1.6 billion Muslims) huge opportunities await those who are willing to meet the demands for Muslim-friendly hospitality products and services. Muslim tourist expenditure growth is estimated to be approximately 4.79% per annum on average from 2012 – 2020 and by the year 2020, growth in Muslim travel is expected to touch 4.8%, significantly higher than the global figure of only 3.8%. It is also revealed that of the Top 20 countries exhibiting the largest growth in tourism expenditure between 2005 –2010, 25% is from Muslim-majority OIC-member countries. Offering tourism products and services that are Shariah-compliant opens them up to this increasingly affluent tourist market that would otherwise not spend their money on them, thus enabling the products and services to be enjoyed by everyone, i.e. both non-Muslims and Muslims. Among the factors that increase the opportunity in Muslim friendly hospitality services in Malaysia covers various sectors such as transportation, tourist arrival points such as airport, accommodation, dining, prayer facilities and ground handling. Realising the great economic gain offered by the industry and the huge potential offered by Muslim friendly tourism hospitality services certain countries such as Malaysia, Indonesia, Thailand, Australia, New Zealand government and related tourism hospitality agencies play a proactive role to enhance products and services which are suitable for Muslim tourist. Steps are taken to enhance the infrastructure in the industry. Hence, in order to do so it is important to know and understand its requirements and the needs of the Muslim travellers particularly. The discussion will be divided into three main parts as follows.